Association analysis of suicide risk assessed with Mini International Neuropsychiatric Interviews’ Suicidality Module in adolescents with non suicidal self injury disorder - Geng, Shuo; Zhang, Wen; Gao, Xiang; Qu, Lele; Zheng, Xueping; Sun, Jian; Xu, Mingdong; Lin, Hua; Jia, Xueyu; Zhang, Xu (Frontiers in Psychiatry, 2025)
ObjectiveMany adolescents with non suicidal self injury disorder have suicidal ideation. However, the specific characteristics of adolescents with NSSI-D that contribute to high suicide risk remain unclear. This study observes the association between depressive and anxiety symptoms and suicide risk among adolescents with non suicidal self injury disorder, and explores the mechanism underlying the high risk of suicide in this population.MethodAdolescents with non suicidal self injury disorder and their parents from a psychiatric outpatient clinic were selected to conduct paper questionnaires to measure their sociodemographic conditions. The Mini International Neuropsychiatric Interviews’ Suicidality Module(MINISM) was used to assess suicide risk of participants. The Self-Rating Depression Scale(SDS), Self-Rating Anxiety Scale(SAS), and Piers-Harris Children’s Self-Concept Scale(PHCSS) were used to measure depressive and anxiety symptoms, and self-concept of adolescents with non suicidal self injury disorder. According to the high suicide risk cutoff value of MINISM, the sample was divided into high suicide risk group and non-high suicide risk group. We performed descriptive and correlation statistical and network analysis to study the types of depressive and anxiety symptoms associated with suicide risk and the mechanism underlying suicide risk among non suicidal self injury disorder adolescents.ResultsA total of 112 non suicidal self injury disorder adolescent participants were included in this study. Severe depressive symptoms(OR=8.205, 95%CI=3.454-19.490) and severe anxiety symptoms(OR=3.926, 95%CI=1.613-9.554) are associated with a high risk of suicide. The father’s college/university education(p<0.01) is associated with severe anxiety symptoms, and low self-concept(p<0.01) is associated with severe depressive symptoms. Network analysis suggests the centrality of anxiety symptoms and father’s education level.ConclusionThe results of statistical analysis suggest that severe depressive symptoms are related to the high risk of suicide (based on MINISM) in adolescents with NSSI-D statistical significantly, and anxiety symptoms and low self-concept are associated with depressive symptoms in NSSI-D adolescents. Interventions targeting anxiety symptoms in adolescents with NSSI-D may help reduce their suicide risk.